Detection of chiral enantiomers via an optical fibre sensor. Issue 3 (6th February 2021) - Wang, Maoyan; Li, Hailong; Zou, Guangzhe; Liu, Yu; Yu, Mengxia; Li, Guiping; Zhang, Xiaochuan; Xu, Jun
Abstract : We report a method to detect chiral enantiomers via an optical thin-film coated long-period ﬁbre grating sensor. To simulate such circularly layered structure containing magneto-electric coupling enantiomers, the theory for wave propagation in lossy thin-film coated fibres expanded by separating cladding modes into left and right circular polarization. The applicable conditions and solving process of complex effective refractive indices for the cladding modes are discussed. The behaviours of the complex refractive index of the lossy sensing film, optical activity and refractive index of enantiomers, mode and period of the grating on sensing characteristics of the sensor are theoretically clarified. By simultaneously observing variations of dual resonance wavelengths and minimum transmissions of the sensor, the refractive index-induced and chirality-induced changes can be distinguished. This work may provide sufficient guidelines to explore the design and application of long-period ﬁbre grating chirality sensors in industrial, environmental, and biochemical sensing.